MacAB-TolC Contributes to the Development of Acinetobacter baumannii Biofilm at the Solid–Liquid Interface - Robin, Brandon; Nicol, Marion; Le, Hung; Tahrioui, Ali; Schaumann, Annick; Vuillemenot, Jean-Baptiste; Vergoz, Delphine; Lesouhaitier, Olivier; Jouenne, Thierry; Hardouin, Julie; Potron, Anaïs; Perrot, Valérie; et al. (Frontiers in Microbiology, 2022)
Acinetobacter baumannii has emerged as one of the most problematic bacterial pathogen responsible for hospital-acquired and community infections worldwide. Besides its high capacities to acquire antibiotic resistance mechanisms, it also presents high adhesion abilities on inert and living surfaces leading to biofilm development. This lifestyle confers additional protection against various treatments, and allows it to persist for long periods in various hospital niches. Due to their remarkable antimicrobial tolerance, A. baumannii biofilms are difficult to control and ultimately eradicate. Further insights into the mechanism of biofilm development will help to overcome this challenge and to develop novel antibiofilm strategies. To unravel critical determinants of this sessile lifestyle, the proteic profiles of two A. baumannii strains (ATTC17978 and SDF) grown in planktonic stationary phase or in mature solid-liquid (S-L) biofilm were compared using a semi-quantitative proteomic study. Of interest, among the 69 common proteins determinants accumulated in the two strains at the S-L interface, we sorted out the MacAB-TolC system. This tripartite efflux pump played a role in A. baumannii biofilm formation as demonstrated by using ΔmacAB-tolC deletion mutant. Complementary approaches allowed us to get an overview of the impact of macAB-tolC deletion in A. baumannii physiology. Indeed, this efflux pump appeared to be involved in the envelope stress response occurring in mature biofilm. It contributes to maintain WT membrane rigidity and provides tolerance to high osmolarity conditions. In addition, this system is probably involved in the maintenance of iron and sulfur homeostasis. MacAB-TolC might help this pathogen facing and adapting to deleterious conditions occurring, in mature biofilms. Increasing our knowledge of A. baumannii biofilm formation will undoubtedly help us develop new therapeutic strategies to tackle this emerging threat to human health.